Environmental, Genetic, and Behavioral Associations with the Incidence of Obesity in Primary School Children: A Systematic Review - Annisa, Nurul; Sulistyawati, Sulistyawati; Mulasari, Surahma Asti (Epidemiology and Society Health Review (ESHR), 2024)
Background: Obesity is influenced by complex interactions between environmental, genetic, and behavioural factors. This study aims to explore the relationship between these three factors and the incidence of childhood obesity. Method: A systematic literature review was used following PRISMA guidelines. The data were collected from three main databases: Google Scholar, PubMed, and Garuda. Screening was carried out from 89 articles found until 10 relevant articles were obtained for analysis. Results: The analysis shows that childhood obesity is influenced by genetic factors, behaviour (including eating habits and physical activity), and environment (such as access to healthy food and sports facilities). These three factors interact to increase the risk of obesity. Conclusion: This study emphasizes that obesity prevention requires a multidisciplinary approach that involves the roles of family, school, government, and community. Recommended efforts include improving access to nutritious food, education on healthy lifestyles, and creating an environment that supports physical activity. The findings provide important insights for designing more effective interventions to address obesity in primary school-aged children.